Choice of payment instrument for low-value transactions in Japan - Hiroshi Fujiki; Migiwa Tanaka (Deutsche Bundesbank, 2017)
In this paper, we examine the determinants of the choice of payment instrument for low-value day-to-day transactions. Using Japanese household data from 2007 to 2014, we find that three payment instruments, namely, cash, electronic money, and credit cards, comprise the major payment choices for transactions with values less than 1,000 yen (about 8.7 euros). We also find that high-income, financially sophisticated households in urban areas tend to use both electronic money and cash. Further, family households choosing electronic money and cash do not have higher cash holdings compared with family households exclusively choosing cash, holding all other variables constant. We obtain weak evidence that single-person households choosing electronic money and cash have higher cash holdings compared with single-person households exclusively choosing cash, holding all other variables constant.
Keywords: E41; 330; cash demand; electronic money